PERFORMANCE ANALYSIS OF A STEAM TURBINE POWER PLANT AT PART LOAD CONDITIONS - Karakurt, A. Sinan; Gunes, Umit (YILDIZ TECHNICAL UNIV, 2017)
Power consumption highly increases which is related with the growing of the industrial plants and daily using. Increasing power demand can be supplied with building up more efficient plants or optimized old power plants. One of the most important items of a power plant is steam turbine which is designed according to defined parameters (inlet pressure and temperature, flow rates, outlet pressure and power) which also effect the dimensions and performance of the turbine. Turbine loses and irreversibilities are minimum and so efficiencies and power generation are maximum at design conditions. However, power plants always have to operate at off-design or part-load conditions because of the changing of power demands and drop outs of the turbines and other items of the plants. In this study, it is aimed to analyses the isentropic efficiency of a high pressure steam turbine and thermal efficiency of power plant at different load conditions. Analyses showed that both steam turbines and power plant performance were reduced when the power plant operates at partial load conditions.
Keywords: Off design conditions; thermal efficiency; isentropic efficiency; power plant; steam turbine; OFF-DESIGN; FLOW; COMPUTATION; Thermodynamics